Financial Markets (Dis)Integration in a Post-Brexit EU - Pesendorfer, Dieter. author. aut Link
V, 377 p.
Keywords: The European Union is creating a Financial Union with a European Banking Union and a Capital Markets Union in reaction to lessons learned from incomplete financial markets integration, the Global Financial Crisis and European Sovereign Debt Crisis. This book critically analyses these projects for a more integrated, resilient and sustainable financial system at a time when the United Kingdom as the member state with the most developed capital markets and the leading global and European financial center, the City of London, is leaving the Union. Neoliberal financial globalization and markets integration policies have led to finance-led capitalism that caused the crises. By building on pre-crises integration ideas, the Union revives and expands the reach of capital markets-based financing and shadow banking. The book discusses the consequences of deeper integration and the future of European financial centers advocating an alternative financial markets integration based on theories explaining finacialization and finance-led capitalism. Dieter Pesendorfer is Senior Lecturer in Regulation in the School of Law, Queen’s University Belfast, UK. His research focus is on financial regulation.